2002
DOI: 10.1053/jpro.2002.125192
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional accuracy of dental casts: Influence of tray material, impression material, and time

Abstract: Accurate casts can be made with either stock trays or custom trays. An impression made from polyether should be poured only once and within 24 hours after impression making, because of the distortion of the material over time. Silicone impression material has better dimensional stability than polyether. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
(47 reference statements)
1
17
0
1
Order By: Relevance
“…One considerate aspect that has not yet been researched in detail is the proper selection of the impression trays for implant impressions for completely edentulous situations [22–27]. The accuracy of the resultant impressions, however, is contingent to the combination of the impression material and tray used.…”
Section: Introductionmentioning
confidence: 99%
“…One considerate aspect that has not yet been researched in detail is the proper selection of the impression trays for implant impressions for completely edentulous situations [22–27]. The accuracy of the resultant impressions, however, is contingent to the combination of the impression material and tray used.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective in stock tray fabrication is to provide a rigid tray, which provides retention for the impression material 38 . Many studies 2,30,37,39–41 have reported that custom trays provide more accurate dental casts than stock trays, but if stock trays are properly oriented, the impression thickness is uniform, and stock trays can give a better result than custom trays 14 …”
Section: Discussionmentioning
confidence: 99%
“…One hour after the impressions were set, each of the 40 impressions was treated with a surface‐reducing agent (debubblizer; Prima Dental Products, Mumbai, India) 14 . The impressions were poured with high‐strength dental stone (type IV, Kalrock, batch no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations